0737 Obstructive Sleep Apnea: A Distinct Physiological Phenotypic Risk Factor in older adults with Cognitive decline and Alzheimer's disease. (27th April 2018) - BUBU, O M; Andrade, A; Hogan, M M; Umasabor-Bubu, O Q; Mukhtar, F; Sharma, R A; Miller, M; Mbah, A; Borenstein, A; Mortimer, J; Kip, K; Morgan, D; et al.
Abstract: Introduction: Studies suggest that Obstructive Sleep Apnea (OSA) in the elderly may result in varying functional outcomes relative to OSA in the middle-aged. Therefore, understanding and appreciating the heterogeneity of OSA and its outcomes in distinct age-groups especially at it relates to cognition, subsequent cognitive decline and Alzheimer disease (AD), is critical in mitigating the deleterious effects of OSA. Methods: In this study, we integrated data from over 3 decades of research examining OSA and cognition; OSA and subsequent cognitive decline; and OSA and AD, with particular focus in appreciating the heterogeneity of OSA and its outcomes in distinct age-groups. A systematic literature search of bibliographic databases including PubMed/Medline, Embase, Psych INFO and Cochrane library for clinical trials, was conducted to identify all eligible studies (published from their onset up until August 31, 2017) that examined associations between OSA and cognitive function, OSA and subsequent cognitive decline, and OSA and AD Results: Thirty-four studies examining the association between OSA and cognition, 7 studies examining the association between OSA and subsequent cognitive decline, and 15 studies examining the association of OSA and AD or AD pathology were identified by the literature search after applying specific inclusion and exclusion criteria. The data suggests that OSA is associated with greater cognitive deficits in middle-age adults than in older adults and the elderly; greater risk of subsequent cognitive decline in middle-aged adults than in older adults and elderly; and in older adults with MCI rather than in healthy older adults, OSA may be the critical correlate of cognition. Conclusion: OSA may be age-dependent in older adults (60 - 70 years old) and the elderly (70 years and above) and is associated with neurodegenerative diseases particularly, cognitive decline and AD. In the middle-aged (30 - 60 years old), the data suggests that OSA may be age-related and presents with a distinct phenotype, with cardiovascular, and possibly metabolic effects. Intermittent hypoxia and sleep fragmentation are two main processes by which OSA induces neurodegenerative changes. Support (If Any): None.